Analisis Penerapan Regulasi Serta Penegakan Hukum Persaingan Usaha: Studi Perbandingan Indonesia, Malaysia, Thailand - Lutfi, Muhamad Fauzi Rais; Solapari, Nuryati (Universitas Suryakancana, 2025)
AbstractThis study examines the implementation of competition law regulation and enforcement in Indonesia through a comparative legal approach with Malaysia and Thailand. The research focuses on identifying both similarities and significant differences in regulatory frameworks, institutional authority, and enforcement mechanisms in fostering fair and competitive business environments. This study employs normative legal research using a comparative law approach, based on the analysis of statutory regulations and competition law enforcement practices in the three countries. The findings indicate that Indonesia, Malaysia, and Thailand have adopted modern competition law regimes that prohibit anti-competitive agreements and the abuse of dominant positions, while entrusting enforcement to independent competition authorities. Nevertheless, notable differences remain in terms of institutional structure, scope of authority, and enforcement effectiveness, which influence the level of competition protection in each jurisdiction. Accordingly, regulatory strengthening and policy adjustments in competition law enforcement are essential for Indonesia to enhance fair and effective market competition.AbstrakPenelitian ini menganalisis penerapan regulasi dan penegakan hukum persaingan usaha di Indonesia melalui pendekatan perbandingan hukum dengan Malaysia dan Thailand. Kajian ini berfokus pada persamaan dan perbedaan substansial dalam kerangka regulasi, kewenangan lembaga persaingan usaha, serta mekanisme penegakan hukum dalam menciptakan iklim persaingan usaha yang adil dan kompetitif. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perbandingan hukum yang didasarkan pada analisis peraturan perundang-undangan dan praktik penegakan hukum persaingan usaha di ketiga negara. Hasil penelitian menunjukkan bahwa Indonesia, Malaysia, dan Thailand sama-sama mengadopsi model hukum persaingan usaha modern, melarang perjanjian anti persaingan dan penyalahgunaan posisi dominan, serta menugaskan lembaga independen sebagai penegak hukum persaingan. Namun demikian, terdapat perbedaan signifikan dalam aspek kelembagaan, cakupan kewenangan, dan efektivitas penegakan hukum yang berdampak pada perlindungan persaingan usaha. Oleh karena itu, penguatan regulasi dan penyesuaian kebijakan penegakan hukum menjadi penting bagi Indonesia.